2022
DOI: 10.1042/bsr20212584
|View full text |Cite
|
Sign up to set email alerts
|

Microwave radiation induces neuronal autophagy through miR-30a-5p/AMPKα2 signal pathway

Abstract: The potential health hazards of microwaves have attracted much more attention. Our previous study found that 2856 MHz microwave radiation damaged synaptic plasticity and activated autophagy in neurons. However, the mechanisms underlying microwave induced autophagy were still unclear. In the present study, we established neuronal damage models by exposing rat hippocampal neurons and rat adrenal pheochromocytoma (PC12) cell-derived neuron-like cells to 30 mW/cm2 microwaves, which resulted in miR-30a-5p (“miR-30a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Our group previously established stable animal models to evaluate the nonthermal effects of microwaves ( Supplementary Figure S2 ), and the nonthermal effects on the hippocampus, heart, and testis were evaluated. Our data suggested that power-density-dependent injuries could be detected in these tissues [ 10 , 25 , 48 , 49 ]. In this study, we exposed rats to a multifrequency microwave of 1.5 GHz and 2.8 GHz, the body temperature was monitored both before and immediately after exposure, and no obvious changes were observed.…”
Section: Discussionmentioning
confidence: 94%
“…Our group previously established stable animal models to evaluate the nonthermal effects of microwaves ( Supplementary Figure S2 ), and the nonthermal effects on the hippocampus, heart, and testis were evaluated. Our data suggested that power-density-dependent injuries could be detected in these tissues [ 10 , 25 , 48 , 49 ]. In this study, we exposed rats to a multifrequency microwave of 1.5 GHz and 2.8 GHz, the body temperature was monitored both before and immediately after exposure, and no obvious changes were observed.…”
Section: Discussionmentioning
confidence: 94%
“…However, there are few studies on microwave irradiation’s positive regulation of neuronal activity. Studies have found that microwave radiation damages the synaptic plasticity of neurons and activates neuron autophagy, thereby impairing learning and memory [ 43 , 44 , 45 , 46 ]. In summary, mid-infrared or THz waves with the appropriate frequency and intensity can enhance neuronal function.…”
Section: Discussionmentioning
confidence: 99%
“…The CNS was determined to be the most vulnerable to microwave radiations [ 68 ], with the hippocampus being particularly sensitive [ 69 , 70 , 71 , 72 ]. Specifically, microwaves can damage the brain (one of the two key components of the human CNS), particularly affecting the neurotransmitters which play an important role in passing signals inside the body [ 73 ].…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%
“…Notably, these findings offer insight into observing the combined effects of different frequencies that are commonly present in the atmosphere. Elsewhere, recent in vivo and in vitro studies have reported that microwave radiation causes autophagy in neuronal cells by activating the miR-30a/AMPKα2 pathway [ 71 ]. Furthermore, evidence supports the presence of nonthermal effects and exposure difficulties for the blood barrier of the brain [ 114 ], with 1.5 and 2.856 GHz microwave radiation exposure inducing a decline in spatial memory [ 115 ].…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%